2021
DOI: 10.1016/j.pmedr.2021.101338
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity in Finnish and Swedish speaking Finns; association with daily habits and socioeconomic status – Nordic EpiLung cross-sectional study

Abstract: Multimorbidity is an emerging public health priority. This study aims to assess the role of lifestyle and socioeconomic status in the prevalence of multimorbidity and chronic diseases by using two language groups that are part of the same genetic subgroup but differ by daily habits. We conducted a cross-sectional survey in 2016 with randomly selected population sample with 4173 responders (52.3%) aged 20–69 years in Western Finland. We included 3864 Finnish participants with Swedish (28.1%) or Finnish (71.9%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Our findings that adults with multimorbidity and co-occurring MSK pain experience more adverse effects at baseline than those without also aligns with previous literature which has shown that such individuals generally report higher levels of disability [ 4 , 6 , 59 , 60 ], mental health problems [ 61 63 ], poorer workability [ 6 , 7 , 64 , 65 ], physical inactivity, and obesity [ 5 , 66 , 67 ]. With this complex clinical picture and the cumulative burden of all these conditions, it is not surprising that people with multimorbidity also report higher illness perception, poorer pain self-efficacy, and lower general health.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings that adults with multimorbidity and co-occurring MSK pain experience more adverse effects at baseline than those without also aligns with previous literature which has shown that such individuals generally report higher levels of disability [ 4 , 6 , 59 , 60 ], mental health problems [ 61 63 ], poorer workability [ 6 , 7 , 64 , 65 ], physical inactivity, and obesity [ 5 , 66 , 67 ]. With this complex clinical picture and the cumulative burden of all these conditions, it is not surprising that people with multimorbidity also report higher illness perception, poorer pain self-efficacy, and lower general health.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, 31 studies can be considered largely atheoretical, without any emphasis on pathways through which socioeconomic disadvantage leads to multimorbidity. In the 33 studies applying a theory, the following theories were referred to: behavioural,10 34 35 37 38 40–42 46 51–53 59 71 72 79–82 materialist38 41 42 45 46 48 50 52 71 72 74 79 82–85 and psychosocial 34 42 51 52 57 72 73 82 84–86. In addition, four studies applied a theoretical construct called ‘sense of coherence’, which indicates an individual’s coping capacity to deal with life and stressful events,87 and is an indicator of self-efficacy and psychosocial well-being (consistent with psychosocial explanations),73 and also encompasses social capital51 and social support,57 which are widely considered as psychosocial assets (table 3).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that adults with multiple chronic conditions and concurrent musculoskeletal pain tend to report increased levels of disability, mental health issues, reduced work capacity, physical inactivity, and obesity [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Given the intricate clinical presentation and the combined impact of all these conditions, it is unsurprising that individuals with multimorbidity also experience a heightened perception of illness, diminished pain self-efficacy, and reduced overall health [ 30 ].…”
Section: Discussionmentioning
confidence: 99%